1993
DOI: 10.1366/0003702934067108
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Measurements of Size and Velocity Distributions of Aerosol Droplets from a Direct Injection Nebulizer

Abstract: Aerosol droplet sizes and velocities from a direct injection nebulizer (DIN) are measured with radial and axial spatial resolution by phase Doppler particle analysis (PDPA). The droplets on the central axis of the spray become finer and their size becomes more uniform when ≍ 20% methanol is added to the usual aqueous solvent. This could explain why the analyte signal is a maximum at this solvent composition when the DIN is used for inductively coupled plasma-mass spectrometry (ICP-MS). Mean droplet velocities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…Aerosol particle velocity will impact the aerosol distribution throughout the root system, impacting uniformity of aerosol capture efficiency Shum et al (1993) Hygroscopicity The chemical composition of an aerosol will determine its reaction to changes in the relative humidity of the surrounding gas phase. Water will evaporate out of, or condense into, the droplet in response to imbalances between the water activity of the droplet and root chamber environmental conditions Changes in droplet size distribution.…”
Section: Productivity Within Aeroponic Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosol particle velocity will impact the aerosol distribution throughout the root system, impacting uniformity of aerosol capture efficiency Shum et al (1993) Hygroscopicity The chemical composition of an aerosol will determine its reaction to changes in the relative humidity of the surrounding gas phase. Water will evaporate out of, or condense into, the droplet in response to imbalances between the water activity of the droplet and root chamber environmental conditions Changes in droplet size distribution.…”
Section: Productivity Within Aeroponic Cultivationmentioning
confidence: 99%
“…Aerosol droplet size may change after generation Increases in size distribution introduce variation in deposition efficiency across the root system. Larger droplets are more likely to deposit on roots close to the point of aerosol generationShum et al (1993); Nuyttens et al…”
mentioning
confidence: 99%
“…Shum et al [199] studied the change in mean drop diameter versus the aerosol cone axial position. They found that at 4 mm from the nebulizer nozzle, the aerosols produced by the DIN were generally finer than those measured just at the exit of the nebulizer.…”
Section: Direct Injection Nebulizer (Din)mentioning
confidence: 99%
“…In contrast, a high-sensitivity analytical system for trace elements in ultralow volume samples, such as specic living cells, is expected to provide insight into cancer generation mechanisms and differentiation processes of pluripotent cells. Direct injection nebulizers (DINs) [4][5][6] and direct injection high-efficiency nebulizers (DIHENs) [7][8][9][10][11] have been developed to reduce sample consumption. These nebulizers reduce the memory effect and enhance the sample introduction efficiency.…”
mentioning
confidence: 99%